2016
DOI: 10.1080/09638288.2016.1238967
|View full text |Cite
|
Sign up to set email alerts
|

Access to publicly funded outpatient physiotherapy services in Quebec: waiting lists and management strategies

Abstract: Our findings provide evidence that a large number of persons wait a long time for publicly funded physiotherapy services in Quebec. Based on our results, implementation of a prioritization process with an initial evaluation and intervention could help improve timely access to outpatient physiotherapy services. Implications for Rehabilitation Access to publicly funded outpatient physiotherapy services is limited by long waiting times in a great proportion of Quebec's hospitals. The use of a specific prioritizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 53 publications
1
38
0
Order By: Relevance
“…For people with OA, exercise advice is typically provided by physical therapists, and of all allied health professionals in Australia, general practitioners most frequently refer patients with OA to physical therapists . However, many people experience significant challenges accessing physical therapy services , including difficulties obtaining referrals or appointments, long waiting times , and limited availability of care in some regional or remote areas . People with knee OA who have difficulties accessing appropriate health care often delay seeking care , possibly to the detriment of their symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…For people with OA, exercise advice is typically provided by physical therapists, and of all allied health professionals in Australia, general practitioners most frequently refer patients with OA to physical therapists . However, many people experience significant challenges accessing physical therapy services , including difficulties obtaining referrals or appointments, long waiting times , and limited availability of care in some regional or remote areas . People with knee OA who have difficulties accessing appropriate health care often delay seeking care , possibly to the detriment of their symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Some patients may not even receive services due to waiting times or restricted eligibility criteria [4], while others face long delays before receiving services. Our research team found the median waiting time for publicly funded physiotherapy services in Québec, the second most populous province in Canada, to be 140 days [3], which is higher than the reported waiting time in Ontario [2]. In 2015, there were a total of 18,245 patients on the waiting lists for these services across Québec [3].…”
Section: Introductionmentioning
confidence: 71%
“…Our research team found the median waiting time for publicly funded physiotherapy services in Québec, the second most populous province in Canada, to be 140 days [3], which is higher than the reported waiting time in Ontario [2]. In 2015, there were a total of 18,245 patients on the waiting lists for these services across Québec [3]. Managing waiting lists is a challenge [5] and waiting list managers use various strategies in order to help them in this task.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations